2021
DOI: 10.3390/textiles1010005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Acoustic Properties of Natural-Fiber-Based Materials and Composites: A Review

Abstract: Recently, very rapid growth has been observed in the innovations and use of natural-fiber-based materials and composites for acoustic applications due to their environmentally friendly nature, low cost, and good acoustic absorption capability. However, there are still challenges for researchers to improve the mechanical and acoustic properties of natural fiber composites. In contrast, synthetic fiber-based composites have good mechanical properties and can be used in a wide range of structural and automotive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…3. Three-dimensional reinforcement, has a higher isotropic strength than the previous two types [19], [20].…”
Section: Cannabis Sativa Fibermentioning
confidence: 91%
“…3. Three-dimensional reinforcement, has a higher isotropic strength than the previous two types [19], [20].…”
Section: Cannabis Sativa Fibermentioning
confidence: 91%
“…103 Table 7 provides the Industrial standards of natural fiber composites for sound absorption applications. ; Hassan et al 94 ; Das et al 95 ; Kudva et al 96…”
Section: Natural Fibers In Nfrhcsmentioning
confidence: 99%
“…The friction between the movement of the air particles and the cavities within the material enables the sound kinetic energy to be converted into heat energy and the sound is attenuated. [14][15][16][17][18][19] Silica aerogels prevent the sound reflection by allowing sound to penetrate their open cavities or channels and help to absorb the sound. 14,15,20 Fricke et al [2001] reported that the speed of sound in aerogels is lower than air (100 ms À1 ), which is about one-third of the velocity of sound in air, and they have exceptional sound properties.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] Silica aerogels prevent the sound reflection by allowing sound to penetrate their open cavities or channels and help to absorb the sound. 14,15,20 Fricke et al [2001] reported that the speed of sound in aerogels is lower than air (100 ms À1 ), which is about one-third of the velocity of sound in air, and they have exceptional sound properties. 21 Forest et al [2001] reported that the smaller granules allow to increase the attenuation and to reduce the velocity of sound in the material due to the reduction of the air volume fraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation